Emerging agents for the prevention of treatment induced neutropenia in adult cancer patients. (2nd April 2016) - Matikas, Alexios; Georgoulias, Vassilis; Kotsakis, Athanasios
ABSTRACT: Introduction : The administration of myeloid growth factors is the only approved treatment for the prevention of chemotherapy induced neutropenia and febrile neutropenia. However, their specific indications and contraindications and potential side effects limit their application to only a relatively small subset of patients at the highest risk for complications, such as infection. Areas covered : A computerized systematic literature search was performed through Medline, Google Scholar, Cochrane Library, the Pharmaprojects database and the clinicaltrials.gov website. The shortcomings of the existing treatment approach are reviewed, along with a synopsis of the characteristics of novel agents that protect bone marrow progenitors from the cytotoxic effects of antineoplastic treatment that may be used in the future as a stand-alone preventive strategy or as an adjunct to growth factors. Expert opinion : There is an abundance of agents undergoing evaluation for the prevention of treatment-induced neutropenia. The appropriate selection of patients, the optimization of the use of existing agents and the increasing competition from biosimilars which likely ensure future decreases in healthcare costs are essential for growth factors to retain their dominant position in this setting.